Influence of lightweight expanded perlite and vermiculite on the properties of ground granulated blast furnace slag and fly ash-based mortar / Tie Tzer Sheng - Tie, Tzer Sheng (2021)
The production of cement is highly energy-intensive and contributes to 7% of total worldwide CO2 emission which can cause the environmental problem and threaten to the earth’s atmosphere. Adopting supplementary cementitious materials (SCM) can help to reduce the dependency on cement in moving towards the use of sustainable construction materials. Increasing calls for more efficient construction materials also encourages the use of lightweight materials. Hence, this research is carried out to investigate the influence of lightweight aggregate, namely expanded perlite (EP) and expanded vermiculite (EV), in terms of the key and functional properties of ground granulated blast furnace slag (GGBS) and fly ash-blended mortar. As mechanical strength is not the prime consideration in mortar, high volume of the lightweight aggregate (>50%) as sand replacement was promoted. Likewise, SCM such as GGBS and fly ash is also utilized as substantial amount of partial cement replacement (>30%) for the sustainability of the mortar. The framework of this research was categorized into two phases, where Phase I focuses on the determining the combination of materials (SCM and lightweight aggregate) to obtain suitable mix based on targeted density (1400kg/m3 to 1600kg/m3) and 28 days strength (≥ 5.17MPa). The mortars mixed with 50% lightweight fine aggregate (EP or EV) with or without the use of 30% SCM (GGBS or fly ash) could achieve the targeted density and strength. Based on this, the mortars are categorized as Mortar Type N with Density Class D1.6, while the mortars mixed with 50% EP as sand replacement can be categorized as soft mortar due to higher flow diameter (≥200mm) than EV mortar. Response surface methodology (RSM) was also found to be useful to provide the mathematical prediction equation for density and strength and optimize the mix design of the lightweight mortar. The mortars which achieved targeted density and strength were then selected for further investigation in Phase II. In Phase II, the key properties (flow, water retention, density, compressive strength and water sorptivity) and functional properties (sound absorption and solar reflectance) of the selected mortars were evaluated. All selected mortars mixed with the lightweight aggregates (50% EP or EV) with or without 30% SCM showed high water retention (≥91%), while mortars with EP showed the highest flow diameter. In overall, among the investigated mortars, the lightweight mortar mixed by 30% GGBS as cement replacement with 50% EP as sand replacement presented the best combination as it had adequate fresh properties (flow = 232mm and water retention = 92%), achieved the targeted density (1460kg/m3) and strength (5.8MPa), lowest sorptivity (0.947mm.min-0.5), exhibited good sound absorption coefficient (α = 0.26 and NRC = 0.17) and high solar reflectance index (SRI = 0.63). Compared to conventional mortar, the mix is good for echo sound or noise absorption and imparts addition features such as solar heat or solar light reflection when applied as building material.